Analysis of Occupational Accidents in Various Informal Sectors in Indonesia - Widowati, Evi; Wahyuningsih, Anik Setyo; Seftyono, Cahyo; Sulistyani, Ummi Nur Laila; Kurniawan, Muhammad; Dwijaningtyas, Srinata; Hapsari, Roro Retno Sri; Rahayu, Octavia (Universitas Negeri Semarang (UNNES) in cooperation with the Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2024)
Occupational Safety and Health (OSH) protection is the fundamental right of every worker and a legal component that should be implemented in the workplace, including the informal sector. Many informal sectors in Indonesia still have high potential hazards; including those related to the work environment, chemical substance management, inadequate knowledge of employers and workers, non-compliance with OSH standards, and suboptimal prevention of work-related accidents and illnesses. This study aims to analyze the OSH conditions in the informal sector and their influence on occupational accidents in various informal sectors in Indonesia. The study adopts an analytical observational design with a cross-sectional design, using purposive sampling technique. The selected informal sectors include paint workshops, batik, furniture and salons. An interesting finding from this research indicates that the variable influencing occupational accidents in the informal sector is chemical hazards, with a significance value <0.05, i.e., 0.035, and Exp (B) of 64.188, meaning that workplace chemical hazards affect the occurrence of occupational accidents 64.188 times more. Therefore, intensive supervision and guidance regarding the work environment, especially chemical substance management, must be continuously enhanced.